Are observed associations between a high maternal prepregnancy body mass index and offspring IQ likely to be causal?. Issue 10 (29th July 2019) - Coo, Helen; Fabrigar, Leandre; Davies, Gregory; Fitzpatrick, Renee; Flavin, Michael
Abstract : Background: A high maternal prepregnancy body mass index has been associated with lower offspring IQ, but it is unclear if the relationship is causal. To explore this, our objectives were to compare maternal and paternal estimates and to assess whether certain factors mediate the association. Methods: We analysed data from the Avon Longitudinal Study of Parents and Children, which initially recruited 14 541 women residing in Avon, UK, with an expected date of delivery in 1991–1992. Data were collected during and after pregnancy by questionnaire, medical record abstraction and clinical assessment. At approximately 8 years of age, psychologists administered an abbreviated form of the Wechsler Intelligence Scale for Children-III. We fit multivariable logistic regression models to estimate parental prepregnancy obesity and overweight–offspring IQ associations. Counterfactually defined indirect (mediated) effects of maternal prepregnancy obesity on offspring IQ were estimated through path analysis. Results: Among 4324 mother–father–child triads and using normal weight as the referent, we observed consistently stronger associations for maternal prepregnancy obesity and offspring performance IQ (eg, adjusted β (95% CI)=−3.4 (−5.7 to −1.2) vs −0.97 (−2.9 to 0.96) for paternal obesity). The indirect effects of maternal obesity on offspring IQ through pathways involving gestational weight gain and duration of breastfeeding were small but significant. Conclusion: Our findings are consistent with a weak biologic effect of maternal adiposity in pregnancy on offspring performance IQ. Given the growing prevalence of obesity worldwide, more evidence is needed to resolve the correlation versus causation debate in this area.